(untitled) (Global Journal of Human-Social Science, 2024)
The history of Intangible Heritage Convention which dates back to the late 19th century involves the intensive collection of old objects the construction of museums the preservation of monuments and the foundation of National Heritage Protection Programs in order to preserve locally rooted culture at all costs Modern museums were described as a colonial legacy in Cameroon This has posed a problem to indigenous museums commonly referred to as openair museum in Kedjom Keku as they remain unsung because of the innovations introduced by the European concept of museology Indigenous museum constitutes of artisanal workshop ecological sites and institutional photos like family album religious institution traditional architecture and monuments Today the paradigm has shifted to mean a building in which objects of historic scientific artistic or cultural interest are stored or exhibited This paper looks at the significance of indigenous museums as veritable tools in preserving Kedjom Keku cultural heritage